(untitled) (Journal of Entrepreneurship and Business, 2024)
The spread of the COVID-19 pandemic has changed daily life greatly. As a result of the restrictions implemented during the spread of COVID-19, most transactions were undertaken online. All economic sectors, including the Micro, Small, and Medium Enterprises (MSME) sector, were affected by the new norms. At the beginning of the COVID-19 outbreak, online transactions were challenging to implement. Nevertheless, they are becoming easier and help entrepreneurs maintain consistent operations until the economic situation becomes stable. The MSME sector is crucial in comparison with other primary sectors in the acquisition of national income. This review article discusses the impact of the adoption of e-commerce platforms among MSME entrepreneurs based on three aspects of technology, organisation, and environment in a recovering economy after the spread of the COVID-19 pandemic. The three primary aspects of the technology, organisation, and environment (TOE) model are widely adopted in the study of e-commerce platform adoption. In the future, this study will continue with the methodology, findings, and discussion sections.